Surgical Ventricular Septal Defect Repair - Emmanuelle Fournier, MD; Bastien Provost, MD; Alice Dirickx, MD; Estibaliz Valdeolmillos, MD; Gregoire Albenque, MD; Clément Batteux, MD; Viktoria Weixler, MD, PhD; Sébastien Hascöet, MD, PhD; Emre Belli, MD, PhD (JACC: Case Reports, 2025)
Ventricular septal defects (VSDs), the most common of congenital heart defects, vary widely in anatomy and size. Surgical treatment of very large VSDs can be challenging because no clear recommendations exist about which defects can undergo biventricular repair with septation and which should instead be palliated. Although Fontan circulation is known to be associated with long-term morbidity, information is limited about how ventricular septation of large VSDs affects cardiac function. This case series describes the successful ventricular septation of 3 patients with large VSDs and the lessons we learned in treating them.